The Strategy Planning Process Strategic Analyses, Objectives, Options and Projects - Grünig, Rudolf; Kühn, Richard; Morschett, Dirk (Springer International Publishing : Imprint: Springer, 2022)
XVIII, 271 p. 135 illus.